A comprehensive and systematic review on resveratrol supplementation as a promising candidate for the retinal disease: a focus on mechanisms of action from preclinical studies - Lv, Xiao-Min; Li, Na; Chen, Lin-Wei; Sun, Cheng (Frontiers in Pharmacology, 2025)
BackgroundResveratrol is a natural polyphenolic compound that shows great potential in neuroprotection, anti-inflammation,and antioxidation. Previous studies have demonstrated that resveratrol can effectively treat various animal models of retinal diseases.PurposeThe aim of the research was to use an animal experimental model to assess the effectiveness of resveratrol in treating retinal-related diseases in various animal models of retinal diseases such as ischemia-reperfusion injury, diabetic retinopathy, glaucoma, chronic ocular hypertension, optic neuritis, age-related macular degeneration, and retinopathy of prematurity. Furthermore, this study aims to reveal the underlying mechanisms of resveratrol related to the treatment of retina-related diseases.MethodsA search was conducted across several databases, including PubMed, EMBASE, the Cochrane Central Register of Controlled Trials, Web of Science, and OVID. The search time was from the establishment of the database to October 2024 to collect studies on resveratrol intervention in animal models of retinal diseases. The studies included in this paper adopted the SYRCLE’s risk of bias tool. Stata 16.0 and RevMan 5.4 software were used to analyze and visualize the results.ResultsOur meta-analysis comprises 26 studies and 365 animals demonstrates the following effects of resveratrol compared to the control group: a significant increase in the number of retinal ganglion cells (SMD = 3.91, 95% Cl = [2.97, 4.86], p < 0.00001) and superoxide dismutase activity (SMD = 3.14, 95% Cl = [0.96, 5.33], p = 0.005). Moreover, a decrease in malondialdehyde (SMD = −9.29,95% Cl = [−12.84, −5.74], p < 0.00001), reactive oxygen species level (SMD = −4.29,95% Cl = [-6.25, −2.32], p < 0.0001), cyclooxygenase-2 (SMD = −2.66, 95% Cl = [−4.01, −1.30], p =0.0001), tumour necrosis factor-α(SMD = −3.96,95% Cl = [−6.27, −1.65], p = 0.0008) and interleukin-6 (SMD = −3.32,95% Cl = [−4.20, −2.44], p < 0.00001) was observed. The A-wave amplitude and B-wave amplitude showed an increase respectively (MD = 105.92,95% Cl = [58.99, 152.84], p < 0.00001); (MD = 158.00,95% Cl = [86.35, 229.65], p < 0.0001), along with an increase in inner retinal thickness (SMD = 6.33, 95% CI = [5.10, 7.56], p < 0.00001) and total retinal thickness (SMD = 2.70, 95%Cl = [0.77, 4.83], p = 0.01). Subgroup analysis showed that different doses of resveratrol were associated with an increase in the number of RGCs (p < 0.05). Resveratrol improves retinal diseases through multiple mechanisms: i) Neuroprotection: it activates the SIRT1/NF-κB and Nrf2 pathways, inhibits Caspase-3 expression, and promotes the survival of RGCs and ii) Antioxidation: it upregulates SOD activity, reduces the levels of MDA and ROS, and alleviates oxidative damage and iii) Anti-inflammation: it inhibits the COX-2, TNF-α, IL-6, and NF-κB pathways, alleviating the inflammatory response. These mechanisms resulted in enhanced amplitude of A/B waves, improved retinal thickness and visual function.ConclusionResveratrol has neuroprotective, anti-inflammatory and antioxidant effects through multiple mechanisms, thereby reducing retinal damage and maintaining the structure and function of the retina. This provides preclinical support for its possible therapeutic uses in the management of retinal diseases.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/myprospero.